Direct plasma printing of nano-gold from an inorganic precursor. Issue 21 (9th May 2019) - Hong, Jungmi; Yick, Samuel; Chow, Edith; Murdock, Adrian; Fang, Jinghua; Seo, Dong Han; Wolff, Annalena; Han, Zhaojun; van der Laan, Timothy; Bendavid, Avi; Ostrikov, Kostya (Ken); Murphy, Anthony B.
Abstract : A direct one-step nano-gold printing process from a HAuCl4 solution precursor is demonstrated using an atmospheric-pressure plasma jet. Abstract : Plasma printing and plasma-assisted printing of functional nanomaterials are being developed as important alternative fabrication techniques. Nano-gold is used in many applications including organic photovoltaics, flexible electronics, nanomedicine, catalysis and sensing, taking advantage of its unique optical, electrical and physical properties, which depend on particle shape, size and distribution. A direct one-step nano-gold printing process using an HAuCl4 solution precursor injected into an atmospheric-pressure plasma jet is demonstrated. Atomized droplets of the solution are reduced to gold nanoparticles in the plasma and deposited on the substrate. The gold film has minimal Cl content, and its structure can be controlled by the deposition time, from nanometer-size particles to a dense film that fully covers the substrate. Printing is demonstrated on substrates including silicon, alumina filter membrane, vertical graphene, and paper. The applicability of the nano-gold film as a SERS (surface-enhanced Raman scattering) platform is demonstrated by sensing of a 0.25 and 0.7 amol μm −2 of Rhodamine B on an Si and paper substrate respectively, a level undetectable in the absence of nano-gold.